DEVELOPING A WORKER ENGAGEMENT MATURITY MODEL FOR IMPROVING OCCUPATIONAL SAFETY AND HEALTH (OSH) IN CONSTRUCTION - Kenneth Lawani; Billy Hare; Iain Cameron (Journal of Construction Project Management and Innovation)
Research on worker engagement (WE) has identified the increased importance of meaningful discussion, communication, knowledge sharing, and shared decision-making regarding occupational safety and health (OSH) practices within the construction industry. This paper reports on initial findings on the development of a meaningful discussion framework for improving OSH and engagement of the construction workforce. The main purpose of the framework is to rank levels of discussion amongst construction operatives and supervisors related to positive performance at work and enhancement of OSH. This reflects the legal and ethical requirements for management to collaborate with the construction workforce for the improvement of OSH. For effective WE in OSH to become the norm, the effectiveness of corporate OSH engagement programmes needs to be assessed using a valid and reliable tool. Also, there is a need for a practice-driven and -validated worker engagement maturity model (meaningful discussion framework) that not only identifies and aligns with existing organisational capabilities, as shown in the HSE leadership and worker involvement research, but also addresses a set of dimensions specifically targeted at construction workers. The methods used to develop the framework discussed here involved qualitative interviews to gain accounts of episodes of worker engagement, which were categorised using NVivo and ranked based on feedback from expert focus groups. The meaningful discussion framework highlights the link that higher levels of worker and organisational maturity can have with higher levels of construction OSH performance. This is based on a number of logically progressive worker maturity levels, where higher levels build on the requirements of already existing levels, from discussing issues affecting individual workers to issues that affect other workers, and ultimately to issues “beyond the site gate”, such as design processes. Final validation testing of the model will be reported on at a later date.